2017
DOI: 10.4097/kjae.2017.70.5.555
|View full text |Cite
|
Sign up to set email alerts
|

The safety of endoscopic esophageal procedures under general anesthesia

Abstract: BackgroundWith the increasing demand for general anesthesia for endoscopic esophageal procedures, anesthesiologists should understand the clinical characteristics of post-procedural complications (PPCs).MethodsWe retrospectively investigated the incidence of and risk factors associated with PPCs of endoscopic esophageal procedures performed under general anesthesia from July 2013 to November 2016. The final analysis included 129 patients; 114 who underwent esophageal endoscopic dissection for esophageal tumors… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 18 publications
0
3
0
Order By: Relevance
“…Studies show that aspiration in patients with liver cirrhosis can be minimized during any endoscopic intervention by using safety measures. 22,23 Limitations of the Study: The study demonstrated a high mortality rate primarily contributed by tracheobronchial aspiration, while no other reasons were studied which remains the major limitation of the present study. There may be other possible reasons than the ones studied (age, gender and occurrence of tracheobronchial aspiration) that need to be investigated.…”
Section: Discussionmentioning
confidence: 83%
“…Studies show that aspiration in patients with liver cirrhosis can be minimized during any endoscopic intervention by using safety measures. 22,23 Limitations of the Study: The study demonstrated a high mortality rate primarily contributed by tracheobronchial aspiration, while no other reasons were studied which remains the major limitation of the present study. There may be other possible reasons than the ones studied (age, gender and occurrence of tracheobronchial aspiration) that need to be investigated.…”
Section: Discussionmentioning
confidence: 83%
“…Secondly, tracheobronchial aspiration is observed during massive upper GI bleed which can be prevented by intubating17-20 patients if bleeding patients suddenly collapse. Some cirrhotic patients exhibit aspiration during endoscopic interventions21 which can also be minimized by adequate safety measures 22,23. Mortality from liver diseases is one of the leading cause of death in our country.…”
Section: Discussionmentioning
confidence: 99%
“…Currently, efforts are being made to provide anesthesia services in the endoscopic unit. Aside from sedation for EGD, general anesthesia is also being offered in the endoscopic unit by a dedicated team of anesthesiologists with extensive experience in gastrointestinal endoscopy [47]. Yang et al [13] supported the feasibility of POEM performed by an endoscopist in the endoscopic unit.…”
Section: Future Of Anesthetic Management For Poemmentioning
confidence: 99%